First report of Diplodia mutila associated with Botryosphaeria canker and dieback of apple trees in Xinjiang, China - Sha, Shuaishuai (Plant disease, 2022)
Apple (Malus pumila Mill.) is an important fruit crop in Xinjiang, China. In September 2021, apple tree canker was observed in a 21-year-old commercial apple orchard cv. Fuji in Xinjiang (38°17'51.43"N, 77°9'50.81"E) , northwest of China. Of the 200 plants surveyed, 25% were symptomatic. The diseased trees showed branch dieback and cankers. The cankers observed on the wood were sunken, shriveled, and discolored. After the bark was peeled off, the diseased wood was dark brown, and the necrosis was obvious on the cross-section of the diseased branch. To identify the causal agent, five symptomatic trees were collected and analyzed in the laboratory. Apple wood samples (0.5×0.5 cm) were surface-disinfected with 1% v/v sodium hypochlorite and 75% v/v ethanol, rinsed with sterile distilled water, transferred onto potato dextrose agar (PDA), and incubated in the dark at 25 °C for 5 days. Conidia were induced on sterilized pine needles covered with 2% w/v water agar under near-UV light. The colonies of five isolates were white to gray with sparse aerial mycelium that gradually became dark olive green in the later stage. Conidia were initially hyaline but becoming brown at maturity, 1-septate, oval, rounded at both ends, and with dimensions of 24.9-32.1 × 15.1-21.5 µm (n =50) and the aspect ratio of 1.6. Based on the cultural and morphological features of Phillips (2002), the isolates were identified initially as Diplodia mutila (Fr. : Fr.) Mont. To confirm species identification, genomic DNA was extracted from the representative isolate SC-8A. The primer ITS1/ITS4, EF1-728F/EF1-986R and BT2a/BT2b were used to amplify the rDNA sequences of, respectively, the internal transcribed spacer (ITS), translation elongation factor 1-alpha (EF1-α) gene, and a portion of beta-tubulin (tub2) gene. The nucleotide sequences indicated ≥99% identity to D. mutila (CBS 112553) for three DNA regions. Consensus sequences were deposited in GenBank. as accession numbers OM618108, OM676657 and OM676658 for ITS, EF1-α and tub2, respectively. To fulfill Koch's postulates, pathogenicity tests were performed using isolate SC-8A on one year old branches of cv. Fuji (n=5). Wounds were created in the middle of the branches using a sterilized hole punch (5mm diameter) and were immediately inoculated with mycelial plugs of the same diameter. For the control treatment, sterile agar plugs were used (n=5) in the branches. The inoculated and control branches were wrapped with sterile parafilm. On the 10th day after inoculation, canker lesions appeared on the inoculated branches, but no lesions were observed in the negative control. D. mutila was re-isolated from 100% of the inoculated shoots and was not re-isolated from any of the negative controls, the Koch's postulates were met. Previously, D. mutila has been reported in Canada (Úrbez-Torres et al., 2016), Argentina (Lódolo et al., 2022) and Chile (Díaz et al., 2022) causing Botryosphaeria canker and dieback in apples. To our knowledge, this is the first report of D. mutila causing Botryosphaeria canker and dieback in apple trees in China